The Russia-Ukraine conflict beyond the mainstream narrative - Wick, M. M. M. (9th Annual Conference on Eurasian Politics & Society (IEPAS2022): Conference Programme and Abstract Book, 2022)
The Russia-Ukraine conflict erupted in February 2022 after the Kremlin recognized the independence of the breakaway popular republics of Donetsk and Luhansk. In the aftermath of the recognition of the sovereignty of these entities, the Russian armed forces invaded Ukraine under the justification of the demilitarization and denazification of the neighboring country, as well as to bring to trial those who perpetrated numerous bloody crimes against civilians in the Donbass, including against Russian citizens. Soon after, the international community and the mainstream media began a worldwide campaign against the Russian military action, sympathizing with the government of Kiev. Although Russia is well-known for its information capabilities—whether propaganda, disinformation, or counter-information—the Kremlin appears to have overestimated its ability to wage effective information operations or underestimated the impact of Western brainwashing on public opinion. In addition, the Ukrainian leadership has effectively managed to counter the grounds on which the Russian government has supported its "special military operation." Ukrainian President Zelensky gained the trust, sympathy, and solidarity of Western leaders, the media, and public opinion, presenting his country as the victim of an unjustified aggression. On the other hand, Russian President Putin, excluded from the public debate due to the European Union ban on Russian media, was perceived by the same audience as a gangster. Is this the whole truth, or is there something more beyond the mainstream narrative? This paper aims to offer a factual analysis and a different perspective from the mainstream narrative supported and spread by Western governments and biased media outlets.